Fortalecimento da agricultura familiar na comunidade de Joana Peres, Baião, Pará - RIBEIRO FILHO, Manoel Machado (2021)
The Action Plan deals with the conclusion work of the Ethnodevelopment Course, a proposal that meets a demand from the extractivists of the community of Joana Peres, Baião, state of Pará, for the elaboration of a project focused on agriculture, or more precisely, to the cultivation system. In this sense, from the dialogues and the meeting with the community members, there were some motivating questions for the construction of a proposal to expand the consortium with perennial species and forest essences native to the region and to ensure family income all year round. With the greater diversification of agricultural activities, there will be promotion of employment in the community and consequently encourage people to remain. Based on this dialogue and concerns that the communitary decided to build the proposal to strengthen sustainable family agriculture in the community. Agriculture is development through the traditional system of cutting and burning, and among some cultivated species are the black pepper, açaí, cupuaçu, manioc and rice, planted intercropped or not. In addition to agriculture, to complement the family income, the community members carry out other activities such as extractivism of non-timber forest products, fishing, hunting, creation bovine and others. Institutional partnerships will be sought to reinforce the plan, from the perspective of strengthening ethnodevelopment strategies through the protagonism of families and appreciation of traditional and local knowledge.